EFEK LATIHAN AEROBIK INTERVAL DAN CONTINUOUS TERHADAP KADAR SGOT DAN SGPT PADA TIKUS DIABETES INDUKSI STREPTOZOTOCIN - Adriyanti Kartika Sari; Sapto Adi; Saichudin Saichudin (Jurnal Sport Science, 2016)
Abstract: The purpose of this research is to know the effect of exercise is aerobic interval and continuous with different intensity levels of SGOT and SGPT against using spectrophotometer to measure levels of SGOT and SGPT in mice of diabetes mellitus. Research methods use a random control group posttest only design. Sampling of the research done by dividing the group into 3 groups, each group consisting of 10 rats, with a group exercise program Aerobics workout interval (5%-15% of total body weight), whereas the Group moderate aerobic exercise continuous 2%-5% of total weight). Analysis using a test Post-hoch indicates that Sig. < α, namely 0.059 > 0.05 which means there are no differences in the levels of SGOT, SGPT levels while with Sig. < α meaning 0.000 > 0.005 there is a significant difference between the group's continuous intervals, and control.Keywords: Diabetes mellitus, aerobic Exercise, intervals, Continuous, SGOT and  SGPT Levels.